Analysis of heating degree day requirments changes under climate change in South Khorasan - hossein Imani pour; abdolreza Kashki; mokhtar Karami (تحقیقات کاربردی علوم جغرافیایی)
Heating requirements are one of the most important human issues in the fields of agriculture, tourism and energy management in the present and future .Knowing the extent of these changes can be very effective in making decision makers. The purpose of this study is to examine the changes in the requirements of the heating degree day in conditions of climate change in southern Khorasan province. For this purpose, daily data from the minimum and maximum temperature of 11 stations of the South Khorasan province were received from the Meteorological Organization of Iran during the period of 1990-2015. The latest available scenarios of the fifth report of the Climate Change Interagency Panel (AR5 2014) include RCP scenarios from the Canadian Climate Change website and, using the SDSM macroeconomic statistics software, the data for the upcoming period (2016-2046) in the study area was thrown off. Using the Matlab software capability, the monthly and annual heating requirements of the stations were calculated in the current and future period. Finally, using the Kriging interpolation method, the zoning maps for cooling requirements for the current and future period are mapped in ArcGIS software. By examining the effect of geographic features (latitude and longitude and station height) on the heating needs in the area, it was determined that the role of heights is very effective in changing the heating needs. In the cold months of the year (Azar, Dey and Bahman), the highlands (Qain, Arsak, Fath Abad, Aryan Shahr, Darmian) require higher energy levels due to the need for higher temperatures. Increasing the temperature and warming of the air in the future, especially in the months of Farvardin and Mehr in most places, requires less use of exhaustible equipment in the future.